On Resisting State Crime: Conceptual and Contextual Issues - Friedrichs, David O. (Social justice, 2009)
In this article the author discusses the criminology of state crime. It is noted that crimes of state are greater in scope than those crimes committed by individual offenders. A number of issues are addressed including transnational crime, supranational criminology, crime and social harm, and global and comparative criminology. Also examined is resistance to state criminality, the cost to community and society of state crimes, core concepts contained in supranational criminality, and resistance to state crime in a globalized world.